A new species of bunchgrass lizard (Squamata: Phrynosomatidae) from the southern sky islands of the Sierra Madre Occidental, Mexico - Grummer, Jared A.; Bryson Jr., Robert W. (Zootaxa, 2014)
A new species of bunchgrass lizard in the Sceloporus scalaris group is described from the southern portion of the Sierra Madre Occidental in Mexico. The new species, Sceloporus aurantius sp. nov., was previously confused with S. brownorum but differs from this and all but one species within the S. scalaris group by a lack of blue belly patches in males. It shares with S. chaneyi an absence of blue belly patches, but differs from this species in size, number of dorsal scales, number of scales around midbody, and presence of an un-patterned morph. The new species further differs from S. chaneyi, and all other species in the S. scalaris species group, by unique phylogenetic position revealed through species delimitation based on multi-locus nuclear DNA. Principal component analyses of 24 traditional morphological characters used to describe previous S. scalaris group taxa indicate that these characters may be of limited use to delineate species in this species group. However, male lateral and ventral coloration may still be an important character for diagnosing species.